Association of Decreased Enhancement of Nasoseptal Flap on Postoperative Magnetic Resonance Imaging with the Risk of Complication - Wingrove, Peter M.; Arani, Keerthi N.; Snyderman, Carl H.; Gardner, Paul A.; Cabral, David T. Fernandes; Zenonos, Georgios A.; Wang, Eric W.; Chabot, Joseph; Fernandez-Miranda, Juan C.; Chang, Yue-Fang; Hughes, Marion A. (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives Our objective was to determine if decreased contrast enhancement on postoperative magnetic resonance imaging (MRI) is associated with an increased risk of complication in patients who have undergone nasoseptal flap (NSF) reconstruction.Design/Setting This was a single-institution retrospective study of patients who underwent a first-time endoscopic endonasal approach (EEA) with NSF reconstruction.Participants Patients underwent an EEA to the skull base with NSF reconstruction and received postoperative MRI within 3 weeks of the operation.Main Outcome Measures MR exams were scored on the degree of contrast enhancement at first postoperative MRI. An enhancement score of 4 indicated ≥75% enhancement of the NSF. A score of 3 indicated enhancement ≥50% and <75% enhancement of the NSF. A score of 2 indicated ≥25% and <50% enhancement of the NSF. Complications (e.g., cerebrospinal fluid [CSF] leak, meningitis, empyema, cerebritis, brain abscess, flap necrosis, and flap migration) were retrieved from our institution's skull base database. Logistic regression was used to determine the effect of the MRI enhancement score on the odds of developing a complication.Results Out of 99 patients in the study, six had complications. Patients who underwent NSF reconstruction of skull base defects were found to have 19 times higher odds of complication (p = 0.007) if they had had an NSF enhancement score of 2 on their postoperative MRI when compared with patients with complete or near complete NSF enhancement (score 4).Conclusion Quantifying NSF enhancement with an MRI may help surgeons better predict which of their patients are at an increased risk of complication.
Keywords: complication; endoscopic endonasal; nasoseptal flap; EEA surgery; skull base reconstruction